1997
DOI: 10.1111/1467-9817.00025
|View full text |Cite
|
Sign up to set email alerts
|

Are Structured Abstracts Easier to Read Than Traditional Ones?

Abstract: Background: Structured abstracts (which contain sub-headings such as this one) have replaced traditional abstracts in most current medical journals. Evaluation studies have shown that such abstracts usually contain more information, are of a higher quality, and facilitate peer review.Aim: The aim of the studies reported here was to investigate an additional, but as yet unexamined, feature of structured abstracts ± namely whether or not they might be easier to read.Method: Eight studies were carried out. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 13 publications
1
25
0
1
Order By: Relevance
“…We also performed some initial analysis at this stage, in that values of the Flesch Reading Ease measure and Gunning Fog Index were recorded for each document (Flesch 1948;Flesch-Kincaid Readability Test 2006;Automated Readability Index 2006). While in (Hartley and Sydes 1997) the authors note that these metrics ignore many factors, they do also observe that when applied to two versions of the same abstract then the results should provide some indication of whether or not one version might be easier to read than the other. The length of each index (in words) was also recorded.…”
Section: On-line Data Collectionmentioning
confidence: 99%
“…We also performed some initial analysis at this stage, in that values of the Flesch Reading Ease measure and Gunning Fog Index were recorded for each document (Flesch 1948;Flesch-Kincaid Readability Test 2006;Automated Readability Index 2006). While in (Hartley and Sydes 1997) the authors note that these metrics ignore many factors, they do also observe that when applied to two versions of the same abstract then the results should provide some indication of whether or not one version might be easier to read than the other. The length of each index (in words) was also recorded.…”
Section: On-line Data Collectionmentioning
confidence: 99%
“…It has been found that structured abstracts are of higher quality than traditional, unstructured abstracts, but that they are longer. They are more readable and more informative, their contents can be assessed quicker and more easily, they are easier to search and recall, and they facilitate peer review [12,18,19,21].…”
Section: Use Case Descriptionsmentioning
confidence: 99%
“…However, while some research has found that this type of scaffold fosters knowledge development (e.g., Jonassen et al 1986;Hartley and Sydes 1997), other research has found limited benefit of providing students with guiding questions during learning with hypermedia. For example, Azevedo and colleagues (2005) found that young students who received conceptual scaffolding, in the form of 10 domain specific questions designed to guide their learning about the circulatory system, demonstrated lower conceptual learning gains from pre-to post-test and used fewer key SRL processes during learning than students who did not receive scaffolding.…”
Section: Self-regulated Learning Theory (Srl)mentioning
confidence: 99%